Determinants of User Trust in Financial Technology Usage in Indonesia - Zahra Hafizha Isaura; Chikita Putri Prameswari; Osly Usman (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
The objective of this research is to examine the variables that influence the level of user confidence when utilizing Financial Technology (Fintech) in Indonesia. There are six hypotheses tested, each of which links the variables of perceived security, knowledge, ease of use, and user experience with user trust in Fintech. Data was collected from respondents who have used Fintech in Indonesia and analyzed using SmartPLS 4 software. The outcome of the research indicated that security perception significantly and positively influences ease of use, while knowledge has a positive and significant impact on user experience, and user experience positively and significantly affects Trust. Nonetheless, the study found no significant influence of security perception and knowledge on trust. The implication of these results suggests that Fintech companies operating in Indonesia should consider these factors to promote user trust in their services.